They can do it. Positive Authoritarianism in Poland and Hungary - Wagner, Franziska; Enyedi, Zsolt (Frontiers in Political Science, 2024)
It is often assumed that right-wing authoritarian and populist parties appeal primarily to negative feelings such as frustration, fear or alienation, and that positive sentiments appear in their discourse mostly in the form of nostalgia. Our hypothesis is that this description is frequently incorrect, and it particularly fails to apply to leaders in power. To identify the ratio of positive and negative sentiments, and to describe and contextualize the nature of detected positive messages the article analyzes the speeches of Viktor Orbán (Fidesz -Hungary) and Jarosław Kaczyński (PiS -Poland). With the help of quantitative and qualitative analyses we find that these leaders devote much attention to the future in their communication and work with various types of positive sentiments such as optimism, pride, and efficacy. A close attention to their rhetorical devices sheds light on the connections between the visions of the past and future and it reveals the way how the positive messages are embedded in the fundamentally conflict-centered and illiberal worldview of the speakers. The article concludes considering a form of right-wing authoritarian politics that is not built on "politics of fear", but (also) on positive affective appeals as a form of emotional governance.